LEVERAGING DIGITAL PRODUCT AND PROMOTION INNOVATION TO ENHANCE COMPETITIVENESS IN SMALL AND MEDIUM ENTERPRISES (SMES) - Astuti, Widi; Ardianto, Hendri; Luwiha , Luwiha (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
This study explores the role of product innovation and digital promotion in enhancing the competitiveness of Small and Medium Enterprises (SMEs). In globalization and digital transformation, SMEs face significant challenges, including shifting consumer preferences and heightened competition. Product innovation is critical in adding value and differentiating SME products. Meanwhile, digital promotion provides a cost-effective avenue for SMEs to reach broader audiences than traditional media. A quantitative research approach was employed, utilizing a survey method targeting SMEs across various sectors. The sampling used the total sampling method, with a sample of 70 people. The total sampling technique was used, and data were collected through Likert scale-based questionnaires. The findings reveal that the synergy between product innovation and effective digital promotion strategies significantly enhances SME competitiveness, increased sales, stronger customer loyalty, and improved market positioning. These results highlight the importance of adopting sustainable innovation practices and leveraging digital platforms strategically to thrive in an ever-changing market landscape. This study offers practical insights for SMEs to strengthen their market presence and maintain a competitive edge.